The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1002/pssa.201600112
|View full text |Cite
|
Sign up to set email alerts
|

Efficient yellow and green emitting InGaN/GaN nanostructured QW materials and LEDs

Abstract: Efficient green emitting LEDs and monolithic white light emitting LEDs require the extension of the range of efficient light emission in the GaN/InGaN materials system. We demonstrate high efficiency green and yellow light emitting multiple quantum well (MQW) structures grown on GaN nanostripe templates. The structures show promise for realizing high efficiency phosphor -free white LEDs. The nanostripe dimensions range from 100 to 300 nm and have separations that range from 300 nm to 1 mm. The MOCVD growth con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…These wavelengths correspond to red, green, and blue colors, respectively. Compared to recent work that demonstrated yellow-and green-emitting monolithic white LEDs grown on GaN nanostripe templates [28,29], the emission spectrum in this work is closer to natural sunlight. To analyze the detailed behaviors of these PL lines, the PL spectra were fitted with Gaussian peaks, and the best fit to the PL data provided both the peak energy and the integrated intensity.…”
Section: Resultsmentioning
confidence: 59%
“…These wavelengths correspond to red, green, and blue colors, respectively. Compared to recent work that demonstrated yellow-and green-emitting monolithic white LEDs grown on GaN nanostripe templates [28,29], the emission spectrum in this work is closer to natural sunlight. To analyze the detailed behaviors of these PL lines, the PL spectra were fitted with Gaussian peaks, and the best fit to the PL data provided both the peak energy and the integrated intensity.…”
Section: Resultsmentioning
confidence: 59%
“…Increasing the luminescence efficiency in the green [1][2][3] or longer wavelength range [4][5][6] is one of the most important subjects for the research and development of InGaN-based light-emitting diodes (LEDs). Usually, the luminescence efficiency of LEDs is evaluated using the external quantum efficiency (EQE).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the QW width and composition varied on the {10-11} planes, leading to emitted light changing from blue to yellow along the planes of the pyramidal nanostructures. Nanosheet/nanostrip green LEDs were fabricated by Nakajima et al, 247 with dimensions ranging from 100 to 300 nm. A sharp electroluminescence emission peak was observed from QWs grown on {10-11} facets and blue-shifted from 551.1 to 541.1 nm with increasing injection current.…”
Section: Optoelectronicsmentioning
confidence: 99%